Rehabilitation effects of circuit resistance training in coronary heart disease patients: A systematic review and meta‐analysis. Issue 8 (27th June 2022) - Wu, Chunchun; Bu, Rongsheng; Wang, Yaoguo; Xu, Chaoxiang; Chen, Youfang; Che, Lishuang; Wang, Shengnan
Abstract: Background and Hypothesis: The rehabilitation effect of circuit resistance training in coronary heart disease (CHD) patients remains unclear. We perform this review to examine the rehabilitation effect of circuit resistance training in CHD patients and to provide a basis for the formulation of reasonable individual exercise prescriptions for CHD patients. Methods: Randomized controlled trials (RCTs) were searched on PubMed, Web of Science, The Cochrane Library, Embase, Clinical Trials, and CNKI. About 1232 studies were identified. Nine RCTs were finally used for the present meta‐analysis to determine the rehabilitation effect of circuit resistance training in CHD patients, compared to aerobic training. Individuals enrolled for the studies were at a mean age of 60.5 years old and were all CHD patients. Following the PRISMA guidelines, we extracted basic information about the study and patient characteristics, as well as measurements (e.g., the peak oxygen uptake, the body mass index [BMI], the body fat percentage, the systolic blood pressure, the total cholesterol, and triglycerides). Subsequently, this meta‐analysis determined the overall effect by using standardized mean difference (SMD) and 95% confidence interval (CI). Results: Compared with aerobic training, circuit resistance training significantly decrease the BMI and the body fat percentage. Conclusions: As suggested from the present meta‐analysis of RCTs, circuit resistance training is effective in improving the BMI and the body fat percentage in CHD patients and may help delay the progression of CHD. CRT has the advantage of lower load in most cases with a similar effect.